2017
DOI: 10.4172/2327-5146.1000290
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Association with Severity of White Matter Lesions on Magnetic Resonance Imaging

Abstract: Background: The objective of this study was to identify risk factors involved in the severity of deep subcortical white matter (DSWMH) and periventricular (PVH) hyper-intensities on MRI, which are white matter lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several studies reported that the lesions of white matter (WMLs) are considered as asymptomatic lesions [7,8]. There are two types of WMLs.…”
Section: Editorialmentioning
confidence: 99%
“…Several studies reported that the lesions of white matter (WMLs) are considered as asymptomatic lesions [7,8]. There are two types of WMLs.…”
Section: Editorialmentioning
confidence: 99%